Engaging readers' attention in academic essay writing / Roselina Musahar and Saiful Johari Musahar - Musahar, Roselina; Musahar, Saiful Johari (2016)
The ability to express ideas effectively in academic essay writing requires knowledge of the topic, correct essay structure and elements involved in each structure. One of the important structures in the academic essay is the introduction paragraph whereby in this paragraph the writer should make an effort to engage the interest of the readers to want to read on. Engaging the readers' attention can be achieved by setting the background of the topic written using strategies known as attention getters. Thus, knowing the various techniques of attention getters available to writers and using them effectively are extremely crucial in achieving this purpose. Despite this fact, students are still struggling to write an interesting opening to their essay using the available attention getters, hence, making their essay less appealing to readers even at the start. This study is aimed at investigating English as a second language (ESL) learners' ability in using attention getters as the introduction strategy of their essays. Using content analysis method, participants' essays of a given topic, specifically the introduction paragraph was analysed according to four attention getter strategies which were taught earlier in class. Data was processed using SPSS software version 23 and statistical methods used for analysis were frequency analysis, cross tabulation and chi square tests. Findings reveal that students prefer using a particular attention getter strategy to capture the reader's interest instead of using all strategies available to them. It can be concluded that to enable students to apply all strategies available, they should be encouraged to use different strategy every time essay writing is involved.